Effect Chain Analysis of Supercritical Fuel Disintegration Processes Using an LES-based Entropy Generation Analysis. Issue 11 (1st November 2020) - Ries, Florian; Kütemeier, Dennis; Li, Yongxiang; Nishad, Kaushal; Sadiki, Amsini
ABSTRACT: In this work, a large eddy simulation (LES) technique combined with entropy generation analysis (EGA) is employed in order to investigate the complex physics of fuel injection under supercritical conditions. In particular, physical processes that are relevant for the fuel breakup and mixing are identified and their effects on the overall disintegration process are quantified. Thereby, it turned out that (1) a chain of four consecutive physical processes (shearing, separation, pseudo-boiling, and turbulent mixing) drive the overall jet disintegration, (2) entropy is primarily generated due to thermal energy conversion processes including pseudo-boiling rather than hydrodynamics, and (3) LES technique combined with EGA proved to be a promising approach for effect chain analyses, not only for simple flows, but also for those with complex thermodynamic properties like supercritical fuel injection. Based on these findings, a physical model of the disintegration process of a cryogenic jet flow injected at supercritical conditions is proposed.